Ethical Leadership and Organizational justice: Moderating Role of Conscientiousness - Amna Ali; Adil Adnan; Dr. Muhammad Ayub; Khalid Jamal; Saima Gul; Zaigham abbas; Tauseef urrehman (Elementary Education Online, 2023)
The aim of this study was to find the effect of ethical leadership on organizational justice. This study also finds the moderating role of Conscientiousness on the relationship between ethical leadership and organizational justice. This study was conducted in higher education sector of Khyber Pakhtunkhwa, Pakistan. Cross-sectional research design was used in this studyand n= 300 sample size was selected for this study. The results of the revealed that ethical leadership has positive and significant effect on all types of organizational justice. Moreover, the results also revealed that Conscientiousness has significant and positive moderating effect on the relationship between ethical leadership and organizational justice.